Tattoo Inks for Optical Biosensing in Interstitial Fluid. Issue 21 (12th September 2021) - Pazos, Martalu D.; Hu, Yubing; Elani, Yuval; Browning, Kathryn L.; Jiang, Nan; Yetisen, Ali K.
Abstract: The persistence of traditional tattoo inks presents an advantage for continuous and long‐term health monitoring in point of care devices. The replacement of tattoo pigments with optical biosensors aims a promising alternative for monitoring blood biomarkers. Tattoo inks functionalization enables the control of interstitial biomarkers with correlated concentrations in plasma, to diagnose diseases, evaluate progression, and prevent complications associated with physio pathological disorders or medication mismatches. The specific biomarkers in interstitial fluid provide a new source of information, especially for skin diseases. The study of tattoo inks displays insufficient regulation in their composition, a lack of reports of the related complications, and a need for further studies on their degradation kinetics. This review focuses on tattoo optical biosensors for monitoring dermal interstitial biomarkers and discusses the clinical advantages and main challenges for in vivo implantation. Tattoo functionalization provides a minimally invasive, reversible, biocompatible, real‐time sensing with long‐term permanence and multiplexing capabilities for the control, diagnosis, and prevention of illness; it enables self‐controlling management by the patient, but also the possibility of sending the records to the doctor. Abstract : The replacement of tattoo pigments with optical biosensors enables a minimally invasive, reversible, biocompatible, and real‐time platform with long‐term permanence and multiplexing capabilities for the control, diagnosis, and prevention of illness by monitoring interstitial biomarkers with correlated concentrations in plasma. The interaction of the biomarker with the biosensor produces a signal proportional to the biomarker concentration in the interstitial fluid.